An innovative advance in bone grafting: initial clinical results using a novel integrative bone graft in spinal fusion - Passias, Peter G.; Onafowokan, Oluwatobi O.; Das, Ankita; Mir, Jamshaid M.; Yung, Anthony; Fisher, Max (Frontiers in Musculoskeletal Disorders, 2025)
IntroductionAlthough autologous iliac crest bone graft (ICBG) has long been the gold standard for spinal fusion, complications related to its harvest and availability issues with local bone autograft have encouraged the development of bone graft substitutes that provide safer alternatives with consistent clinical efficacy and potential for applications across musculoskeletal health, including spinal fusion. This study evaluates the initial safety and efficacy of a novel integrative bone matrix (IBM) in spinal fusion procedures.MethodsThe charts of twenty patients who underwent spinal fusion surgery at 1–5 contiguous interbody levels and/or 1–15 contiguous posterolateral levels with the novel IBM between November 2022 and May 2023 were retrospectively evaluated for safety and efficacy endpoints at standard of care 3, 6, and 12 months postoperative follow up visits. Radiographic fusion rate was evaluated by plain radiographs using the Bridwell interbody fusion grading system and/or the Glassman posterolateral fusion grading system, as appropriate. Subjective pain, disability, and quality of life assessments included the EuroQoL 5 Dimensions Visual Analogue Scale (EQ-5D VAS), Oswestry Disability Index (ODI), and the revised Scoliosis Research Society Score (SRS-22r).ResultsNo adverse events occurred that were related to the graft, and no subjects required unplanned revision surgery. Radiographic fusion was achieved in all (100%) of the interbody and posterolateral levels by 12 months. There was no significant difference in overall fusion rate between subjects receiving short vs. long segment constructs. At 3, 6, and 12 month follow up, significant (p < 0.001) improvements were observed compared to baseline values for all patient reported outcome measures, and the cohort reached the minimum clinically significant mean improvements.DiscussionThis study highlights the potential of this novel IBM as a safe and effective bone graft substitute in spinal arthrodesis procedures. Patients had a high rate of fusion without any graft-related adverse events. Larger, controlled studies with longer-term follow-up are warranted for further validation.